2020
DOI: 10.3390/ijerph17176152
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of E-Cigarette Vapor Components on the Morphology and Function of the Male and Female Reproductive Systems: A Systematic Review

Abstract: : E-cigarettes, a comparatively new phenomenon, are regarded as a safer alternative to conventional cigarettes. They are increasingly popular among adolescents of both sexes, and many smokers use e-cigarettes in their attempts to quit smoking. There is little understanding of the effects of exposure to e-cigarette vapors on human reproductive health, human development, or the functioning of the organs of the male and female reproductive systems. Data on the effects of the exposure were derived mainly from anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…A reduction in circulating testosterone levels might also impair normal erectile function. 33 Moreover, human studies have shown a dose −response association between the nicotine concentration in cigarettes and ED, with high-nicotine cigarettes being associated with higher rates of ED than low-nicotine cigarettes. 34 In addition, a meta-analysis reported that the OR for ED was significantly higher among those who smoked 10 cigarettes per day than among those smoking less than that, including an increased risk of ED when considering smoking duration.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in circulating testosterone levels might also impair normal erectile function. 33 Moreover, human studies have shown a dose −response association between the nicotine concentration in cigarettes and ED, with high-nicotine cigarettes being associated with higher rates of ED than low-nicotine cigarettes. 34 In addition, a meta-analysis reported that the OR for ED was significantly higher among those who smoked 10 cigarettes per day than among those smoking less than that, including an increased risk of ED when considering smoking duration.…”
Section: Discussionmentioning
confidence: 99%
“…Rokok elektrik semakin populer di kalangan remaja dan banyak perokok menggunakan e-rokok dalam upaya mereka untuk berhenti merokok. Pemahaman tentang efek paparan asap rokok elektrik terhadap kesehatan reproduksi manusia, perkembangan manusia, atau fungsi organ sistem reproduksi pria dan wanita masih kurang (Szumilas et al, 2020). Pengguna rokok elektrik di Indonesia meningkat secara signifikan.…”
Section: Pendahuluanunclassified
“…Under the proposed rules, the FDA would ban the sale of the products to persons under the age of 18 [3]. Recent studies have highlighted the effects of e-cigarettes on the cardiovascular system [6,7], oral health [8,9], the immune system [10], and other systems [11].…”
Section: Introductionmentioning
confidence: 99%